Analysis and Evaluation of Quality in Urban Open Spaces for Leisure Time (Case Study: Arak City) - Mohammad Kazem Yavari; Alireza Sheakholeslami (جغرافیا و آمایش شهری منطقه‌ای, 2023)
Urban open spaces have great potential for all kinds of urban activities, and one of the important functions of these spaces is leisure time, which has become more important in recent decades due to the rapid growth of urbanization and the revolution that has occurred in the lifestyle of citizens. Dealing with the issue of quality in urban open spaces for spending leisure time, and analyzing and identifying the most important indicators affecting the quality of these spaces can be especially important for managers and urban planners. Therefore, introducing a process that can provide a proper analysis and evaluation of urban open spaces and factors affecting their quality is important and is one of the goals of this research. This research has been carried out using a descriptive-analytical method with a quantitative-qualitative approach and as a case study. In this research, using theoretical foundations, 45 indicators of quality in urban open spaces were introduced (as an evaluation checklist) and then, using the exploratory walking technique, the mentioned indicators were evaluated in selected open spaces of Arak city. The necessary data has been collected. Then, by using a factor analysis structural measurement model, the influence coefficient of each indicator has been calculated as the weight of the criteria. And then, using the weight of each index and TOPSIS technique, the studied open spaces have been compared and ranked. In this way, a practical process for analyzing and evaluating the quality of urban open spaces for leisure time has been introduced. Based on the results, it was determined that the indicators "the existence of areas and facilities for games and excitement for all ages" and "the existence and conditions of cozy and secluded spaces and the facilities for creating climatic comfort" in improving the quality of urban open spaces for spending leisure time, are the most effective indexers. Also, among the studied open spaces in Arak city, the "Laaleh Amusement Park" and " Shohadaye Gomnaam Park" have won the first and second places, respectively, for spending leisure time.